Contextual, Radiological Anatomy (RA) Learning needs Evaluation for Curricular Improvement - Mohamed Ansari, Reshma; Wei Han, Hong; Idris, Sara; Abdul Latiff, Atikah (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: As a part of the MBBS curriculum review exercise, University of Cyberjaya (UoC), Malaysia had come up with a study to investigate the feedback and learning needs pertaining to radiological anatomy (RA) in pre-clinical teaching. MATERIALS AND METHODS: A single-institutional survey of all five-year medical students was done using an adapted instrument which had both open and close-ended questions on the radiological anatomy teaching received so far and the perception on the teaching methods and content. 405 respondents out of 503 (80%) (year 1=115, year 2= 78, year 3=79, year 4=78, year 5=55) replied. There were totally 136 male and 269 female respondents. RESULTS: Though the overall student learning time (SLT) was adequate, year 3 students (62%) reported inadequate radiological anatomy SLT. Pre[1]clinical students (57.5%) reported more of formal radiological anatomy teaching while clinical students indicated informal teaching (Informal: 15.1 %, Even mix of formal and informal: 56.6 %). Female students reported higher response of adequate SLT (69.1%) and formal teaching (46.9%) compared to males. Small group learning such as gross anatomy practical sessions, problem-based learning, clinical skills teaching, and clinical correlates sessions were recommended. Abdomen and thorax were the most preferred regions where radiological anatomy could be explored further. X-ray followed by CT and MRI were the most favoured radiological modalities to learn topographical anatomy. CONCLUSION: The study provided sound feedback on the existing radiological anatomy teaching practices. Data shows stark contrast between the needs of the students and the current practices indicating that it is quite substantial for curriculum review.